Dampak Pendidikan Informal terhadap Perilaku Flexing Anak di Sekolah - Muh. Wahyuddin S. Adam; Anita Wati Tukloy; Laeli Kurniati; Nisda Bahaja; Sasiarin S Husain (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education has become a primary focus in many countries, including Indonesia. Parents play a crucial role in shaping their children's character, but there are still many challenges such as generational differences, busy schedules, and ineffective communication. According to 2022 data from BPS, 75% of parents recognize the importance of character education, yet 60% of children still experience difficulties communicating with their parents.This study emphasizes that character education begins within the family as the first educational institution. Through role modeling, advice, and habits, parents instill moral values in their children from an early age. Informal education—occurring at home and in the community—plays an important role in shaping behavior, including preventing the flexing behavior or excessive showing off, which has become common among students due to the influence of social media and social pressures. Collaboration between family, school, and society is necessary to instill values of simplicity and empathy, so children grow into moral and responsible individuals.According to Creswell (2014), qualitative research is a process to explore and understand the meanings that individuals or groups assign to social or human problems. This process involves methods such as interviews, observations, and analysis of texts or documents.This study aims to deeply understand the phenomenon of the impact of informal education on the flexing behavior of children at SDN 07 Marisa. This approach is chosen because it allows the researcher to explore the perceptions, experiences, and views of informants regarding the informal education received by children and how it influences their flexing behavior in the school environment.